Constitutional principles in relation to the rights of migrant workers to social security in Malaysia: adopting the human rights approach - Mohamad Amin, Noor Shuhadawati; Ab Aziz, Norjihan; Ab Hamid, Zuraini (Asian Economic and Social Society Publications, 2019)
Enactment of the social security laws in Malaysia does not take into consideration the Malaysian Constitution’s constitutional principles. Likewise, the Constitution itself does not specify the provisioning of social security rights. Nevertheless, two provisions are particularly relevant for the recognition of fundamental rights to the migrant workers in Malaysia: firstly, equality of treatment and secondly, prohibition of slavery and forced labour. The concept of equality as enshrined in Article 8 of the Malaysian Federal Constitution states that all persons are equal before the law. Furthermore, Article 6 of the Constitution prohibits any form of slavery and forced labour. Hence, any form of discrimination, slavery, and forced labour to migrant workers cannot be tolerated. First, this paper aims to examine the basic principles of human rights framework in relation to migrant workers. Next, this paper seeks to analyse these constitutional principles in the light of Malaysian social security laws. Due to the lack of constitutional provisioning on social security in Malaysian Constitution, this paper also examines the experience from the South African Constitution because social security in the country has been constitutionally protected. Lastly, the possibility of implementing the same constitutional principles in Malaysian Constitution will be observed by adopting the human rights approach.